RESONANCE PRODUCTION IN PERIPHERAL HEAVY-ION COLLISIONS - Natale, A. A. (World Scientific Publ Co Pte Ltd, 1994)
Heavy-ion collisions at ultrarelativistic energies may be used as a powerful source of photons and pomerons. We compute the rates for pseudoscalar meson production through two-photon and two-pomeron scattering, at energies that will be available at RHIC and LHC. Light mesons will mostly be produced by pomeron fusion at large rates, the two processes are comparable for charmed mesons, while electromagnetic production will be dominant for bottom mesons. We discuss the possibility of observing the reaction gammagamma(PP) --> R --> gammagamma, and comment on the particular case where R could be a scalar resonance at 650 MeV.